Handbook of Pediatric Autopsy Pathology - Gilbert-Barness, Enid.; Debich-Spicer, Diane E.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Pathologists have long recognized that the pediatric autopsy requires great care in technique and dissection to ensure that easily overlooked malformations are recognized and accurate diagnoses are made. Working in the tradition of the master pediatric pathologists, the highly experienced practitioners Enid Gilbert-Barness, MD, and Diane E. Debich-Spicer have created in the Handbook of Pediatric Autopsy Pathology a comprehensive reference guide to the successful performance of pediatric autopsies and the optimal recognition and interpretation of their pathologic findings. The authors cover such major developmental disorders as hydrops, chromosomal defects, congenital abnormalities, and metabolic disorders. The reviews of the organ systems encompass the cardiovascular, respiratory, gastrointestinal, renal, central nervous, and skeletal systems, plus the male and female genitourinary systems, the eye and adnexa, and the thymus, spleen, lymph nodes, and immunodeficiency. Additional chapters address sudden infant death, cytogenetics, the medical and forensic autopsy, special procedures, cultures and infection control, and biological hazards at the autopsy. Numerous standard reference tables, copious illustrations and drawings, and an appendix at the end of each chapter provide a wealth of practical information and bibliographic citations. A value-added compact disk provides color versions of over 400 selected illustrations found in the book. Cutting-edge and detailed, the Handbook of Pediatric Autopsy Pathology offers the prosector unequaled guidance to performing a pediatric autopsy, making an accurate diagnosis, and-where malformations are involved-explaining the implications of possible recurrences in future pregnancies.
General Principles -- General Principles -- Techniques -- Pediatric Autopsy -- Examination of the Human Embryo -- The Placenta -- Developmental Disorders -- Hydrops -- Chromosomal Defects -- Congenital Abnormalities -- Organ Systems and Metabolic Disorders -- Cardiovascular System -- Respiratory System -- Gastrointestinal System -- Liver, Gallbladder, Biliary Tract, and Pancreas -- Renal System -- Male and Female Genitourinary Systems -- Central Nervous System -- Thymus, Spleen, Lymph Nodes, and Immunodeficiency -- Skeletal System -- Eye and Adnexa Sectioning -- Metabolic Diseases -- Special Considerations -- Sudden Infant Death -- Pediatric Forensic Pathology -- Special Procedures -- Infection Control and Biological Hazards in the Autopsy.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology; Electronic books